An analysis of academic leadership behavior from the perspective of transformational leadership - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
After examining the existing studies of administration in higher education, it has been obvious that academic leadership behaviors are significantly determinative in the development of faculty. Considerable debate has emerged over the most suitable model for academic leadership: not surprisingly, one of the conceptual models dominating the literature is transformational leadership. This study proposes to investigate academic leadership behavior from the perspective of transformational leadership. First, this paper reviews transformational leadership as a concept in detail with its four components: Charismatic Leadership, or Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration. Second, the methodological details and the results of the study are explicitly discussed. The Multifactor Leadership Questionnaire (MLQ) is used to measure different components of transformational leadership as a research instrument. The total field under survey consists of 100 participants including research assistants, instructors, associate professors and full professors of different state universities in Turkey. The SPSS 15.0 (Statistical Package for Social Sciences) is applied to analyze the data gathered by the research instrument. In order to determine whether or not there has been any difference among the academics' perceptions of transformational leadership, with its four dimensions, according to gender, age, tenure, and education variables, non-parametric tests are used. As for the results of the study, the level of 5-point Likert scale measuring the administrators' behavior from the perspective of transformational leadership including all four dimensions is once a while. Of the independent variables, only the education variable is specified as a significant factor affecting the academics' perceptions of transformational leadership. In other words, the level of transformational leadership attitude for the ones having bachelor's degree is indicated to be higher than the others, while the levels are indicated as similar for the ones having B.Ed. and M.A. degrees. In the dimensions of Idealized Influence and Inspirational Motivation, the level of PhD graduates' perceptions of transformational leadership is higher than that of M.A. graduates. In the dimensions of Intellectual Stimulation and Individualized Consideration, the levels are specified to be similar between the M.A. and PhD graduates. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Transformational Leadership; Academic Leadership; Components of Transformational Leadership; PERFORMANCE; ATTITUDES